2023
DOI: 10.3390/sports11050102
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Home-Based Tele-Exercise Training Program on the Quality of Life and Physical Performance in Breast Cancer Survivors

Abstract: The number of breast cancer (BCa) survivors has been steadily increasing due to advances in anti-cancer treatments, though these individuals suffer from various cancer- and treatment-related long-term side effects. The present study aimed at investigating the effects of a home-based tele-exercise training intervention on physical- and mental health-associated parameters in BCa survivors. A total of 13 female BCa survivors (age: 58.31 ± 3.13 years, BMI: 25.68 ± 0.62 kg/m2, waist circumference: 96.54 ± 1.84 cm) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…A total of 48 studies were conducted, involving 3,843 subjects from different countries and regions. Of the 48 studies, 13 were from the United States ( 25 , 31 , 34 36 , 39 , 54 , 57 60 , 62 , 66 ), 9 were from Denmark ( 42 , 47 , 64 , 65 , 69 , 70 , 72 74 ), 5 were from China ( 26 , 28 , 48 , 50 , 63 ), 3 were from Australia ( 27 , 29 , 56 ), 3 were from Canada ( 44 , 45 , 71 ), 3 were from Germany ( 37 , 40 , 55 ), 2 were from Belgium ( 30 , 43 ), 2 were from the Netherlands ( 51 , 61 ), 2 were from Norway ( 46 , 53 ), 2 were from Spain ( 38 , 52 ), 1 was from Greece ( 68 ), 1 was from Korea ( 49 ), 1 was from Turkey ( 67 ), and 1 was from Brazil ( 41 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 48 studies were conducted, involving 3,843 subjects from different countries and regions. Of the 48 studies, 13 were from the United States ( 25 , 31 , 34 36 , 39 , 54 , 57 60 , 62 , 66 ), 9 were from Denmark ( 42 , 47 , 64 , 65 , 69 , 70 , 72 74 ), 5 were from China ( 26 , 28 , 48 , 50 , 63 ), 3 were from Australia ( 27 , 29 , 56 ), 3 were from Canada ( 44 , 45 , 71 ), 3 were from Germany ( 37 , 40 , 55 ), 2 were from Belgium ( 30 , 43 ), 2 were from the Netherlands ( 51 , 61 ), 2 were from Norway ( 46 , 53 ), 2 were from Spain ( 38 , 52 ), 1 was from Greece ( 68 ), 1 was from Korea ( 49 ), 1 was from Turkey ( 67 ), and 1 was from Brazil ( 41 ).…”
Section: Resultsmentioning
confidence: 99%
“…Exercise training also can potentially affect QoL in a manner specific to the cancer site, though this connection remains uncertain ( Furmaniak et al, 2016 ). In a recent study on Greek breast cancer survivors, QoL measured through EORTC-QLQ-C30 improved after an 8-week home-based tele-exercise program ( Andrioti et al, 2023 ). However, active treatment leads to deterioration of QoL aspects ( Zamel et al, 2021 ), so just maintaining a steady state in these patients and preventing unfavorable treatment effects might also be considered beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Different aerobic and resistance training combinations have been applied in breast cancer patients reducing fatigue and improving QoL and sleep quality and quantity ( Schutz et al, 2021 ). Moreover, clear evidence in breast cancer survivors indicates a positive effect of exercise on CRF ( Matsuoka et al, 2021 ; Andrioti et al, 2023 ). However, the dose-response potential of exercise prescription in breast cancer patients remains unclear ( Bellissimo Moriah et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that long‐term adherence to aerobic exercise can reduce the occurrence of chronic diseases such as obesity and cardiovascular disease, while also reducing the risk of cancer. [ 109 ] Additionally, some studies have found that exercise can promote apoptosis and autophagy of tumor cells, thereby inhibiting tumor growth and metastasis. [ 110 ] In summary, psychology, nutrition, and exercise regulate tumor development through various mechanisms and signaling pathways.…”
Section: Mechanisms Of Psychology Nutrition and Exercise In Regulatin...mentioning
confidence: 99%